Meta-analysis comparing doublet and single cytotoxic agent therapy as first-line treatment in elderly patients with advanced nonsmall-cell lung cancer. (December 2015) - Wang, ShengFei; Wang, Qin; Tian, Jianhui; Zhou, Zhiyi; Jiao, Lijing; Fu, Yanli; Chen, Sufeng; Zhang, Jie; Xu, Ling
Objective: To perform a systematic review and meta-analysis comparing doublet versus single agent therapy in elderly patients with advanced nonsmall-cell lung cancer (NSCLC). Methods: PubMed® and Cochrane databases, and American Society of Clinical Oncology, World Congress of Lung Cancer, and European Society of Medical Oncology abstracts were searched. Endpoints were overall survival (OS), 1-year survival rate (1-year SR), overall response rate (ORR), and grade 3/4 adverse events. Subgroup analyses were based on chemotherapy regimens and race. Results: Out of 11 studies (13 randomized trials; n  = 2782), doublet therapy was associated with significantly increased OS (hazard ratio [HR] 0.89, 95% confidence interval [CI] 0.83, 0.95), 1-year SR (risk ratio [RR] 1.15, 95% CI 1.04, 1.28), and ORR (RR 1.39, 95% CI 1.39, 1.86) versus single-agents. Chemotherapy regimen-based subgroup analyses favoured platinum-based doublet therapy for OS (RR 0.71, 95% CI 0.60, 0.84), 1-year SR (RR 1.28, 95% CI 1.11, 1.47), and ORR (RR 1.88, 95% CI 1.49, 2.38). Race-based subgroup analyses revealed increased benefit from doublet therapy in Asian populations for ORR (RR 1.70, 95% CI 1.29, 2.23) but not increased survival benefit. Higher incidences of grade 3/4 anaemia (RR 2.23, 95% CI 1.61, 3.09), thrombocytopenia (RR 2.47, 95% CI 1.17, 5.20), and fatigue (RR 1.36, 95% CI 1.06, 1.74) were observed with doublet versus single-agent therapy. Conclusions: Doublet therapy was associated with significantly increased OS, 1-year SR and ORR compared with single agent therapy. Race may be considered when choosing doublet versus single-agent therapy as first-line treatment of NSCLC in elderly patients.